2015
DOI: 10.1128/aem.01751-15
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Photosynthesis in a Glycogen-Deficient glgC Mutant of Synechococcus sp. Strain PCC 7002

Abstract: c Cyanobacterial glycogen-deficient mutants display impaired degradation of light-harvesting phycobilisomes under nitrogenlimiting growth conditions and secrete a suite of organic acids as a putative reductant-spilling mechanism. This genetic background, therefore, represents an important platform to better understand the complex relationships between light harvesting, photosynthetic electron transport, carbon fixation, and carbon/nitrogen metabolisms. In this study, we conducted a comprehensive analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
(52 reference statements)
2
21
1
Order By: Relevance
“…In the absence of glycogen synthesis, glycogen degradation genes are down-regulated. Contrary to a recent proposal [10] based on study in Synechococcus sp. PCC ΔglgC, there are clear similarities between Synechocystis ΔglgC and WT in transcriptional responses associated with nitrogen starvation, indicating that nitrogen status is indeed sensed by the mutant.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In the absence of glycogen synthesis, glycogen degradation genes are down-regulated. Contrary to a recent proposal [10] based on study in Synechococcus sp. PCC ΔglgC, there are clear similarities between Synechocystis ΔglgC and WT in transcriptional responses associated with nitrogen starvation, indicating that nitrogen status is indeed sensed by the mutant.…”
Section: Discussioncontrasting
confidence: 80%
“…Jackson et al recently showed that remaining phycobilisomes in ΔglgC cells of Synechococcus sp. PCC 7002 remain coupled to Photosystem II [10]. This could indicate that the non-bleaching phenotype underlies a difference between the mutant and WT strains in energy distribution between PSII and PSI, which would possibly be reflected in the identity and abundance of extracellular metabolites that appear in nitrogen starved ΔglgC cultures.…”
Section: Phycobilisome Degradation Is Unsuccessfully Executed In the mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the photosystem II centers in a glgC mutant in Synechococcus sp. strain PCC 7002 were protected from degradation because they entered a quiescent under nitrogen starvation (Jackson et al, 2015). The contents of phycobilisome and chlorophyll were almost constant in the all strains in the presence of nitrogen.…”
Section: Degradations Of Phycobilisome and Chlorophyllmentioning
confidence: 94%
“…Dry cell weight was measured as an earlier published protocol [35] with some modifications. Cell culture was centrifuged at 2500g for 10 min, and the pellet obtained was washed twice in 8.25 mM Tris-HCl buffer (pH 8.2).…”
Section: Dry Cell Weight Determinationmentioning
confidence: 99%